Strategi Pengelolaan Perpustakaan Umum Kota Madiun dalam Meningkatkan Minat Baca dan Literasi Masyarakat - Intan Faiza Susanto; Rosta Alanawa Intan Hanafiah; Bilfa Yumna Zalfi Licia (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to analyze the management strategy of the Madiun City Public Library in increasing reading and literacy among the public post-COVID-19 pandemic. Using a qualitative approach with descriptive methods, data collection was conducted through in-depth interviews with librarians, direct observation, and documentation. The results show that the library's organizational structure is under the auspices of the Madiun City Library and Archives Service, which is divided into three strategic areas. The library implements the Dewey Decimal Classification (DDC) classification system in compiling collections managed using INLIS Lite software from the National Library. To address the decline in post-pandemic visits, the library launched various integrated innovative programs such as the "Dewi Puspa" (City Library Tourism Destination) service for children, the free courier-based "Jarimu" (Book Pick-up and Delivery from Your Home) service, and the "Empok Remen" (Teen Writing Group) writing class program. The main obstacles faced include limited physical space, air conditioning capacity, and limited library material processing personnel, which are periodically addressed through Corporate Social Responsibility (CSR) partnerships and regional development budget submissions.